Parental experiences of transformative dialogic reading practice in the home environment. - Mullen, Christine (My University, 2017)
Literacy achievement from birth is supported by many factors. Literature indicates that one‚Äôs culture, socioeconomic status, (SES) and home literacy environment (HLE) are factors that affect language and literacy skills in the early years. The study reported in this thesis examined how parent and child reading engagements and the home literacy experience impact upon emergent literacy and parental expectations for that literacy. The research was undertaken in a rural DEIS school (Delivering Equality of Opportunity in Schools) involving parents and pupils from the Senior Infant class. Parents in a sample group received dialogic reading workshops and participated in daily dialogic reading with their children. Parents in a control group did not receive the training or participate in the daily readings. All participating pupils were tested in relation to their emergent literacy skills, before and after the reading intervention. The results supported the training and practice of dialogic reading among parents and practitioners in the early years. Furthermore the results of the study suggested that the dialogic reading approach was effective in developing children‚Äôs emergent literacy skills. Finally the results strongly concluded that dialogic reading was effective in changing the perceptions, experiences and engagement of the parents and children in the sample group with regard to literacy in the home and school environments.
Master in Education Studies in Early Childhood Education
Keywords: Research Subject Categories; Literacy; Home literacy environment (HLE); Socioeconomic status (SES); Language; Reading